2015
DOI: 10.1515/polyeng-2014-0243
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hybrid nanoparticle with silica sol as the supporter on the crystallization behavior and mechanical properties of isotactic polypropylene

Abstract: Colloidal dispersions of hybrid nanoparticles with silica sol as the supporter (PKSol) were prepared by supporting aromatic phosphate on silica sol via a chemical action with γ -aminopropyltrimethylsilane (KH550) as a linker in wet process for the first time. Dynamic light scattering (DLS) demonstrated that hybrid nanoparticles with an average size of about 200 nm were formed and transmission electron microscopy (TEM) confirmed the presence of the ultrafine silica sols within the hybrid particles, which exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In their work, Juan et al (58) studied the effect of Silica Sol (KSol) nanoparticules on the thermal and crystallization behavior of isotactic PP (iPP). Their DSC cooling thermograms clearly showed that the addition of KSol and 2,2 ′ -methylene-bis (4,6-di-tert-butylphenol) phosphate (MDBP-POOH)-modified Silica Sol (PKSol) could increase the crystallization temperature of iPP, from 116.4°C to 118.8°C and 120.81°C, respectively.…”
Section: Effect On Thermal Characteristicsmentioning
confidence: 99%
“…In their work, Juan et al (58) studied the effect of Silica Sol (KSol) nanoparticules on the thermal and crystallization behavior of isotactic PP (iPP). Their DSC cooling thermograms clearly showed that the addition of KSol and 2,2 ′ -methylene-bis (4,6-di-tert-butylphenol) phosphate (MDBP-POOH)-modified Silica Sol (PKSol) could increase the crystallization temperature of iPP, from 116.4°C to 118.8°C and 120.81°C, respectively.…”
Section: Effect On Thermal Characteristicsmentioning
confidence: 99%
“…The crude MDBP‐POOH immobilized silica sol nanoparticles were synthesized by KH550 as the linker, as illustrated in Scheme . The experimental details were described in our previous work . In order to mask the interference of other substances and further prove the effect the silica‐based nucleating agent for iPP, the crude product was purified by centrifugation at room temperature in the following two steps.…”
Section: Methodsmentioning
confidence: 99%
“…In the previous work, a silica sol‐based nucleating agent for iPP was prepared by supporting aromatic phosphate on silica sol via chemical action with γ‐aminopropyltrimethylsilane (KH550). The hybrid nanoparticle was proved to be an effective nucleating agent of iPP . Through intense research, we found that directly compounding the aqueous silica sol‐based nucleating agent with iPP would corrode the screw acutely during the process of melt extrusion, which limited the application of silica sol‐based nucleating agent in iPP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The products under the trade names NA-11 and NA-21 are typical examples of organic phosphate nucleating agents, which are very important type-α phase NAs for PP. The excellent nucleation effect of the organic phosphate has attracted widespread attention in academic circles [24][25][26][27][28][29]. It has been shown that ADK STAB NA-11 gave the high Tc and stiffness to PP, which was attributed to the optimal epitaxial match between the PP helix and the organophosphate molecules [30,31].…”
Section: Introductionmentioning
confidence: 99%